Health effects of video display terminals. - Welch LS (Journal of the American Academy of Physician Assistants)
There are more than 15 million video display terminals (VDTs) in the United States, and an estimated 3 million units are produced each year. Given the large number of workers exposed to VDTs and the increasing use of VDTs both in the workplace and in homes, it is important to consider the possibility that adverse health effects result from use of this equipment. This article reviews the types and levels of radiation generated by VDTs, the known potential health effects of this radiation, and the health effects resulting from the physical use of VDTs. The steps clinicians should take to evaluate ophthalmologic, musculoskeletal, dermatologic, and reproductive effects of VDT use are outlined.